TEXT MOOD IN WAIJEWA LANGUAGE: A SISTEMIC FUNCTIONAL LINGUISTIC ANALYSIS - Ngongo, Magdalena (e-Journal of Linguistics, 2012)
This paper is based on Hallidayan systemic-functional grammar (1985,1994, 2004) focusing on mood that realizes interpersonal metafunction of meaning. This paper provides answers to the questions, namely (1) how is mood of text using Waijewa language, and  (2) how does mood realize metafunction of interpersonal meaning in text? Based on Sistemic Functional Linguistic (SFL) theory, the mood text in this paper is viewed from mood system, modality, mood structure, and interpersonal metafunction of meaning.This paper used spoken data collected from the observation  of four sessions of proposing to a girl or in Waijewa language called Kette Katonga Weri Kawendo hereon abbreviated to KKWK, practiced in Wewewa society. Based on the data analysis, it is found out that mood system in text consists of indicative and imperative. The indicative covers declarative and interrogative. The declarative consists of exclamation and affirmative. The affirmative type is the most used which consisted of  2.596 (83%) use. This is caused by clauses repetition used by tenors. Whereas, exclamative is the least used which consists of 37 (1.2%) use. This fact indicates that the tenor should keep his background social prestice. The predicate are either followed or preceded by modality. Modalisation were used by groom’s parents, whereas modulation were used by bride’s parents. Mood structure of affirmative is S^P;  exclamative is EW^S^P;  imperative is  P^C/ C^P; yes/no interrogative is P^S)/ (P^C)/  (S^P); and wh-interrogative is QW^ P^S.  Interpersonal metafunction of meaning aims to get information, give information, and to state opinion of decision made, such as choosing mediators, stating and requesting the amount of dowries, stating time for completing dowries, time to take the bride to groom’s place, and time for bride and groom to get marry.
Keywords: mood, tenor, text, Waijewa, SFL